Implementation of Batik Dyeing Tools to Increase the Productivity of the Coloring Process in Batik SMEs - Putri, Chauliah Fatma; Aviv Yuniar Rahman (IJCS: International Journal of Community Service, 2023)
Batik as a work of cultural art in Indonesia is a work that is also attractive for tourist cities such as Malang City. Batik SMEs in Malang City develop batik typical of the region while maintaining traditional manufacturing methods.  UKM Batik Tulis Poesaka Djagad, located in Blimbing Village, Balearjosari Subdistrict, Malang City, is a Batik UKM that is productive in making batik typical of Malang. In the process of strengthening batik colors, it takes a long time for the color strengthening solution to be absorbed perfectly so that it is less effective. The purpose of this community service activity is to apply a color reinforcement tool to UKM Batik Tulis Poesaka Djagad in the hope of speeding up the coloring process so as to increase the productivity of written batik. The stages of this activity include preparation and planning, implementation, monitoring and evaluation. The implementation of training activities on the use of batik coloring process tools involved the owner, the SME batik craftsmen themselves and several other SME batik craftsmen. The results of the application of the coloring process tool can increase the productivity of batik cloth output, especially at the batik coloring process stage and coloring results with better quality.